2015
DOI: 10.2337/db15-0659
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Phospholipid Metabolism Regulates Insulin Sensitivity and Contractile Function

Abstract: Skeletal muscle insulin resistance is an early defect in the development of type 2 diabetes. Lipid overload induces insulin resistance in muscle and alters the composition of the sarcoplasmic reticulum (SR). To test the hypothesis that skeletal muscle phospholipid metabolism regulates systemic glucose metabolism, we perturbed choline/ethanolamine phosphotransferase 1 (CEPT1), the terminal enzyme in the Kennedy pathway of phospholipid synthesis. In C2C12 cells, CEPT1 knockdown altered SR phospholipid compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 50 publications
8
111
1
Order By: Relevance
“…Finally, also phospholipids may contribute to the muscle phenotype because PE has been reported to affect skeletal muscle growth and PC:PE ratio is inversely correlated to insulin sensitivity . Recent studies in mice showed an impaired calcium uptake and muscle weakness when PE is reduced and consequently, the PC:PE ratio is increased . Interestingly, we found that Plin2 down‐regulation, but not Plin2 overexpression, decreased PC:PE ratio due to a strong increase in PE.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Finally, also phospholipids may contribute to the muscle phenotype because PE has been reported to affect skeletal muscle growth and PC:PE ratio is inversely correlated to insulin sensitivity . Recent studies in mice showed an impaired calcium uptake and muscle weakness when PE is reduced and consequently, the PC:PE ratio is increased . Interestingly, we found that Plin2 down‐regulation, but not Plin2 overexpression, decreased PC:PE ratio due to a strong increase in PE.…”
Section: Discussionmentioning
confidence: 47%
“…21,56,57 Recent studies in mice showed an impaired calcium uptake and muscle weakness when PE is reduced and consequently, the PC:PE ratio is increased. 58,59 Interestingly, we found that Plin2 down-regulation, but not Plin2 overexpression, decreased PC:PE ratio due to a strong increase in PE. This phospholipid change may also contribute to the growth-promoting action of Plin2 down-regulation.…”
Section: Discussionmentioning
confidence: 69%
“…A clinical study conducted in lean control and overweight but non‐diabetic patients showed that baseline fasting plasma insulin and HOMA‐IR were positively correlated with erythrocyte membrane phosphatidylethanolamine and phosphatidylcholine content in the whole population . Another clinical study in obese patients, who underwent surgery‐induced weight loss, demonstrated that the mRNA level of choline/ethanolamine phosphotransferase 1 (a key protein in final step of phosphatidylcholine synthesis) was inversely correlated with insulin sensitivity . The ratio of phosphatidylcholine to phosphatidylethanolamine has also attracted much attention.…”
Section: Clinical Evidence For the Association Between Phospholipids mentioning
confidence: 99%
“…In a mouse model, reduced phosphatidylcholine levels mediated by hepatic specific knockout of CT, which is the key enzyme for phosphatidylcholine biosynthesis, were shown to lead to triacylglycerol accumulation but had no effect on insulin sensitivity . However, perturbed phosphatidylcholine synthesis through skeletal muscle specific knockdown of CEPT, the rate‐limiting enzyme in the major route for phosphatidylcholine production, resulted in improved insulin sensitivity in mice treated with a high‐fat diet . This influence on insulin sensitivity was thought to be related to an increase in activation of calcium‐signalling pathways via decreased sarco/ER Ca 2+ ATPase‐dependent calcium uptake (Figure ).…”
Section: Experimental Evidence For the Association Between Phospholipmentioning
confidence: 99%
“…In mice with skeletal muscle-specific knockout of ET, reduction in cellular PE coincided with increased skeletal muscle mitochondrial biogenesis and exercise endurance [35]. In contrast, muscle-specific deletion of CEPT1 had no apparent effect on skeletal muscle mitochondria but promoted muscle weakness [36]. Differences in mitochondrial phenotype promoted by deletion of PSD, ET, or CEPT1 demonstrate the complexity of skeletal muscle phospholipid metabolism.…”
Section: Phosphatidylethanolaminementioning
confidence: 99%